Psychological Predictors of Career Adaptability in University Students: Refining the Adaptive Readiness Model Through A Systematic Review - Rahma, Earlene Tania; Mulyana, Olievia Prabandini (Amkop Management Accounting Review (AMAR), 2025)
Career adaptability has emerged as a critical competency for university students navigating uncertain academic and professional environments. Based on Career Construction Theory, this study methodically examined recent empirical research (2020–2025) to identify psychological predictors of career adaptability among student populations. A comprehensive search of PubMed and ScienceDirect, conducted in accordance with PRISMA 2020 standards, yielded twelve papers that met the inclusion criteria. The findings identified two broad categories of predictors: dispositional factors that align with the theory of adaptive readiness, such as proactive personality, Core self-evaluation, emotional regulation, and emotional skills; and novel predictors that represent the contextual and developmental realities of students, such as academic engagement, thinking styles, peer support, self-reflection, psychological capital, grit, and basic psychological needs satisfaction. Findings suggest that while Rudolph et al.’s adaptive readiness model provides a useful foundation, it requires refinement to integrate motivational, reflective, and contextual processes specific to higher education. According to the study's findings, career adaptability is best seen as a multifaceted concept influenced by social settings, coping mechanisms, and personal characteristics. In order to prepare students for the uncertainties of the job market of the twenty-first century, institutions must provide interventions that enhance both personal resources and relational support.